2017
DOI: 10.1002/2017ea000285
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of Global Precipitation Measurement estimates over the Indian subcontinent

Abstract: Accurate and real‐time precipitation estimation is a challenging task for current and future spaceborne measurements, which is essential to understand the global hydrological cycle. Recently, the Global Precipitation Measurement (GPM) satellites were launched as a next‐generation rainfall mission for observing the global precipitation characteristics. The purpose of the GPM is to enhance the spatiotemporal resolution of global precipitation. The main objective of the present study is to assess the rainfall pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…The one-minute DSD measurements obtained from JWD are fitted with a three-parameter gamma distribution, as suggested by Ulbrich (1983). The details about the DSDs used in the present study can be found in Das et al (2017) and Krishna et al (2017).…”
Section: Instrument and Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-minute DSD measurements obtained from JWD are fitted with a three-parameter gamma distribution, as suggested by Ulbrich (1983). The details about the DSDs used in the present study can be found in Das et al (2017) and Krishna et al (2017).…”
Section: Instrument and Datasetsmentioning
confidence: 99%
“…13.6 GHz and Ka-band at ~35.5 GHz. The details of the satellite mission can be found in Huffman et al (2015), and the dataset used in the present analysis can be found in Krishna et al (2017).…”
Section: Dsd Overview-topographic Perspectivementioning
confidence: 99%
“…Murali Krishna et al (2017) showed that the GPM measurements improved over the Western Ghats region compared to TRMM measurements. They further assessed the DSD measurements from GPM https://doi.org/10.5194/acp-2019-832 Preprint.…”
Section: Effect Of Orography On Raindrop Size Distribution Over Wgsmentioning
confidence: 99%
“…The one-minute DSD measurements obtained from JWD are fitted with a three-parameter gamma distribution, as suggested by Ulbrich (1983). The details about the DSDs used in the present study can be found in and Krishna et al (2017).…”
mentioning
confidence: 99%
“…Moreover, previous studies have assessed the performance of IMERG over varied topographic and geographic features considering seasonal characteristics [19,[21][22][23][24][25][26][27][28][29]. The validation of the IMERG dataset using ground-based observations (i.e., gauges and radar) in conterminous US and Canada suggests an overall improvement in surface precipitation measurement from previous similar products [22,26].…”
Section: Introductionmentioning
confidence: 99%